2011
DOI: 10.1260/2040-2295.2.4.447
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and History of Vitreous Surgery

Abstract: There have been tremendous advances in the small-gauge pars plana vitrectomy (PPV) systems. This review provides an overview of the recent advances and state of the art of vitreous surgery. The two most innovative advancements that have been developed in this area are the small-gauge cutter and the new illuminating systems. Compared to the traditional 20-gauge PPV, transconjunctival sutureless small-gauge PPV is a safe and effective strategy to treat a variety of vitreoretinal diseases. Chandelier illumination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Until quite recently, pneumatic cutters employed a single pneumatic pulse from a pneumatic energy source located in the machine to close the cutter guillotine blade and relied on a spring to open it to complete a duty cycle. Pneumatic cutters were smaller and lighter, but as the mechanical properties of the spring remain constant, as the cut rate increased, the inability of the spring to keep up with the pneumatically driven closure increased the time the port is closed, thereby decreasing the duty cycle [ 46 ].…”
Section: Fluidics Of Vitrectomymentioning
confidence: 99%
“…Until quite recently, pneumatic cutters employed a single pneumatic pulse from a pneumatic energy source located in the machine to close the cutter guillotine blade and relied on a spring to open it to complete a duty cycle. Pneumatic cutters were smaller and lighter, but as the mechanical properties of the spring remain constant, as the cut rate increased, the inability of the spring to keep up with the pneumatically driven closure increased the time the port is closed, thereby decreasing the duty cycle [ 46 ].…”
Section: Fluidics Of Vitrectomymentioning
confidence: 99%
“…Given the continuous evolution of PPV techniques and instrumentation since the early 1970s, we chose to limit our study selection to those conducted from the year 2000 onward. 11 This choice aimed to ensure that this systematic review aligns with contemporary PPV practices and outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the vitreous cutter used in 27-gauge (27G) vitrectomy was expected to present problems like reduced surgical efficiency and shaft stiffness. However, the vitrectomy efficiency improved dramatically by changing the drive system of the vitrectomy machine 3,4 and by developing a bi-blade vitreous cutter 5,6 . Although the debate on shaft stiffness is still ongoing, an increasing number of reports have found that these instruments pose no problem in surgical procedures [7][8][9][10][11] .…”
Section: Impact Of Different Manufacturers and Gauge Sizes On The Permentioning
confidence: 99%